I'm trying to resolve this cauchy problem:

$ y'=2y+1$ such as $y(0)=1$

the general integral for the differential equation is $\frac{1}{2}(e^{2x+2c_1}-1)$

for $y(0)=1$ :


my doubt is about the fact that i don't know how to "get down" that $c_1$ and i can't resolve the problem, can you help me with this one?

Thank you for your time.

  • $\begingroup$ it should be correct! thank you for you help, i'll try to do as you said $\endgroup$ – Gabriele Sortino Apr 27 '18 at 0:41
  • $\begingroup$ If the solution you showed is correct then you simply have to solve: $\frac{1}{2}\left(e^{2C_{1}}-1\right) = 1$ for $C_{1}$. You should get $C_{1} = \frac{ln(3)}{2}$. Sorry for the confusion in the first comment. $\endgroup$ – Desperados Apr 27 '18 at 0:43

$$y(x)=\frac{1}{2}(e^{2x+2c_1}-1)$$ $$t(x)=\frac{1}{2}(e^{2x}e^{2c_1}-1)$$ $e^{2c_1}$ is just a constant $$y(x)=\frac{1}{2}(Ke^{2x}-1) $$ And therefore $$y(0)=1 \implies K=3 \implies y(x)=\frac{1}{2}(3e^{2x}-1)$$


$$y(0)=\frac{1}{2}(e^{2c_1}-1)=1$$ $$\implies e^{2c_1}=3 $$ so substitute to $e^{2c_1}$ its value 3...you don't need to evaluate $c_1$

$$\frac{1}{2}(e^{2c_1}-1)=1$$ $$(e^{2c_1}-1)=2$$ $$e^{2c_1}=3$$ $$e^{2c_1}=e^{\ln 3}$$ $$(c_1= \frac {\ln 3}2)$$

  • $\begingroup$ how do I assign that 3 though?, why is $c_1=\frac{ln(3)}{2} $ ? $\endgroup$ – Gabriele Sortino Apr 27 '18 at 1:06
  • $\begingroup$ ok I derive $e^2x$ right? $\endgroup$ – Gabriele Sortino Apr 27 '18 at 1:08
  • $\begingroup$ for the initial condition remeber that $y(0)=1$ means that when $x=0$ then $y=1$ @GabrieleSortino so yes thats the formula you posted with ln $\endgroup$ – Isham Apr 27 '18 at 1:09
  • $\begingroup$ @GabrieleSortino I added some lines...and yes $c_1= \ln (3 )/2$ $\endgroup$ – Isham Apr 27 '18 at 1:14
  • 1
    $\begingroup$ You are the man, thank you $\endgroup$ – Gabriele Sortino Apr 27 '18 at 1:27

You have $e^{2x+2x_1}=e^{2c_1}\,e^{2x}$. And, whenever you have a "function of a constant", you can think of it as a constant. So your solution is $$ y(x)=\frac12\,(d\,e^{2x}-1). $$ Then $$ 1=y(0)=\frac{d-1}2, $$ so $d=3$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.